Hermeneutical Reconstruction of Qur’anic War Verses: Exclusive Exegesis, Power Relations, and the Challenge of Religious Radicalism in Contemporary Indonesia - Malaka, Andi; Waluyajati, Roro Sri Rejeki; Kustana, Kustana (Integritas Terbuka: Peace and Interfaith Studies, 2025)
This study aims to analyze how exclusive and literalist interpretations of Qur’anic verses on warfare, such as QS. At-Taubah:5and QS. Al-Anfāl:12, have become one of the roots of religious radicalism and to offer a framework for reconstructing interpretation that is more ethical and contextual. The research employs a qualitative-critical approach through library research, using Fazlur Rahman’s double-movement hermeneutics, Michel Foucault’s analysis of power relations, and the framework of maqāṣid al-sharī‘ahas analytical tools. Data were collected from classical tafsirs (al-Ṭabarī, al-Qurṭubī), modern tafsirs (Tafsir al-Azhar, Tafsir al-Mishbāh), and contemporary academic literature. The findings reveal that literalist exegesis, when detached from its historical context and ethical purposes, legitimizes violence and fuels exclusivism, while contextual exegesis offers an inclusive framework that fosters dialogue, reconciliation, and social justice. This study also shows that exegesis is not ideologically neutral but often functions as an arena of power contestation, where interpretation can either reinforce domination or become a discourse of liberation against fundamentalism. The implications highlight the urgent need to integrate contextual hermeneutics into religious education curricula, strengthen exegetical literacy in public discourse, and promote interreligious dialogue as a means to counter radicalism. The originality of this research lies in its interdisciplinary integration of hermeneutics, power analysis, and socio-political context, which provides a comprehensive framework for reinterpreting Qur’anic war verses in a way that is faithful to the text yet responsive to contemporary plural realities.